Il lavoro industriale in un mondo capovolto: interrogativi e sfide - Mario Deaglio (Quaderni di Sociologia, 2008)
The global economy is undergoing extremely rapid structural changes that force researchers to qualify and redefine basic concepts. This paper does not purport to give answer but rather to raise questions. It shows how shifts in GDP and industrial production shares have fundamentally altered the shape of the world economy in the first years of the new century, so that more the share of middle income countries (which include China) in world industrial production has overtaken the share of high income countries. In the meantime the nature of work has altered significantly: human capital can no longer be defined merely in terms of technical skills but increasingly includes elements such as risk-taking and leadership; output is less strictly dependent upon input of work and production is shifting from excludable to non excludable goods. It can therefore be argued that present day work may be fundamentally different in qualitative terms from the traditional category of work employed by economists and sociologists.